'From Bench to Stage': How Life Scientists' Leisure Groups Build Collective Self-Care. (1st October 2020) - Schönbauer, Sarah Maria
ABSTRACT: In today's research environments, scientists have to meet competitive demands in order to pursue a career successfully. Such demands are tangible including the need to move abroad, publish, or win third-party grants. Simultaneously, researchers experience an increasingly individualized and competitive work environment and a lack of collective working relationships. Many scientists in academia have difficulty coping with these demands. There is a need for spaces that allow scientists to cope with today's work life challenges. Two leisure groups on an Austrian science campus – a theatre and an orchestra group – are examples of spaces enabling practices to cope with the demands of academia. By acting and playing music, scientists can relate work and leisure. Through their participation, the scientists not only make room for leisure time in their work life but also construct a professional ideal of a creative and communally oriented scientist and establish a feeling of belonging to a place and its shared history. By aligning work and leisure outside of the laboratory, the leisure group members cope with their individualized and competitive work environment. Thereby, the scientists compensate for the lack of social and creative interaction and build a communally oriented, non-hierarchical, and a creative space in academia.